r67=64

Raise each side of the equation to the 76 power to eliminate the fractional exponent on the left side.

(r67)76=±(64)76

Simplify the right side of the equation.

Simplify the expression.

Rewrite 64 as 26.

r=±(26)76

Apply the power rule and multiply exponents, (am)n=amn.

r=±26(76)

r=±26(76)

Cancel the common factor of 6.

Cancel the common factor.

r=±26(76)

Rewrite the expression.

r=±27

r=±27

Raise 2 to the power of 7.

r=±128

r=±128

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

r=128

Next, use the negative value of the ± to find the second solution.

r=-128

The complete solution is the result of both the positive and negative portions of the solution.

r=128,-128

r=128,-128

r=128,-128

Evaluate r^(6/7)=64